Dodatne nadležnosti kao mehanizam integracije Bosne i Hercegovine / Additional Competences as Integrative Mechanisms for Bosnia and Herzegovina’s Integration - Kurtćehajić, Suad (Pregled: časopis za društvena pitanja / Periodical for social issues, 2014)
Article of Scientific Debate on the Social Processes in Bosnia and Herzegovina on its Path of EU Ascension, 22 April 2014.